Estudo da utilização do óleo de peixe visando à produção de nutracêuticos e biodiesel - Oliveira, Ingryd Cristina de (2017)
The use of waste from the fishing industry is emerging worldwide as a sustainable and attractive raw material alternative in environmental, economic and social aspects. Fish oil contains omega-3 polyunsaturated fatty acids (ω3-PUFA), ingredients in the pharmaceutical industry, in the production of nutraceuticals. On the other hand, it also contains saturated fatty acids (SFA), usable in the biodiesel industry. Given this context, the objective of this dissertation was the study of fish oil aiming its fractionation into saturated and unsaturated fatty acids (UFA). In this sense, the extraction and evaluation of oil from Clupea harengus (OR) residues were carried out through physical-chemical, thermal, and chromatographic techniques. Followed by the optimization of the chemical hydrolysis of the oil through 23 factorial design; and obtaining free fatty acids (FFA) using the conditions determined by planning. These FFAs were characterized, and with these results a new strategy of concentration of ω3-PUFA fatty acids was proposed: chemical hydrolysis, followed by crystallization at low temperatures in two steps in the absence of solvents. The research showed that OR has a high content of UFA (71.81%) and ω3-PUFA (17.44%). However, triacylglycerides are difficult to fractionate. The optimal condition for the hydrolysis found is that the catalyst is at 22% m/m; temperature of 90 oC; and reaction time of 2 h. The hydrolysis was effective, with the acidity index increasing from 7.68 mg KOH/g to 172.22 mg KOH/g, and did not significantly affect the UFA content. Two-step crystallization (10 oC and -10 oC) decreased SFA levels by 39.90%, but there was also a decrease in ω3-PUFA of 11.11%. The overall yield was 54% to 60%. The obtained concentrate can be considered a rich source of UFA with a total amount of 83.43%. Among these, 16.17% are ω3-PUFA and 11.78% are EPA + DHA. Thus, the oil extraction, hydrolysis, and characterization procedures were successful. However, the fractionation procedure of free fatty acids at low temperatures needs further studies.